An advanced short-circuit protection scheme for a bipolar DC microgrid - Kant, Kamal; Ansari, Salauddin; Gupta, Om Hari (Frontiers in Energy Research, 2023)
In order to provide quick and accurate fault detection in a DC microgrid, a new protection strategy is developed in this study. It is based on the multi-resolution analysis of travelling waves. The multi-resolution analysis of travelling waves is carried out using discrete wavelet transform (DWT). The dyadic filter bank theory is used to obtain the DWT coefficient of the voltage travelling wave. The energy of the DWT coefficient is then determined, and the fault will be identified if this energy content exceeds the predetermined threshold value. Initially, the efficacy of the proposed algorithm is verified on a 500 V ring-type bipolar DC microgrid test model, which is developed with MATLAB/Simulink environment. Then the results obtained were later validated with the real-time simulator Opal-RT. The various simulation results indicate that the proposed algorithm can successfully be implemented in both modes, i.e., grid-integrated and islanded. It can also provide protection against high resistance fault (HRF) up to 900 Ω in grid-integrated mode, and up to 1,300 Ω in islanded mode. The operating time of the proposed algorithm is also quite fast, i.e., 0.64 m.